H50 'We must live as if he was not ill': an interpretative phenomenological analysis of spouses' experience facing Huntington's disease. (12th September 2022) - Mégane, Menier; Manceau, Charlotte; Constant, Emilie; Decorte, Éric; Simonin, Clémence; Antoine, Pascal
Abstract : Background: Huntington's disease (HD) is a rare autosomal dominant hereditary neurodegenerative disorder that causes motor, cognitive and behavioural symptoms. As the disease progresses, the affected person will become increasingly dependent in the acts of daily life, requiring the introduction of more and more assistance, which is mainly provided by the spouse. This new role of caregiver affects their experience of physical and mental health due to perceived changes in the partner and marital relationship, the management of neuropsychiatric symptoms and the hereditary nature of HD. Aim: The purpose of this study is to investigate the lived experience of spousal caregivers in the middle stage of HD, in order to understand the specificities of this stage. Methods: Nine spousal caregivers of persons with Huntington's disease at an intermediate stage participated in semi-structured interviews, which were recorded, transcribed, and analyzed using an Interpretive Phenomenological Analysis. Results: Five themes emerged: 'Make it stop for today', 'I need help to hang in there', 'Please, help me to help you', 'I need to be a super caregiver' and 'we are no longer a couple anymore'. These themes highlight a dilemma faced by spouses: live and cope with a pervasive disease that modifies one's role and the couple's relationship, while at the same time trying to pretend that it does not exist. Conclusion: These results highlight important clinical implications with the need to take into account the stage of advancement of the disease in order to offer spousal caregivers support adapted to their real needs.